CULTURAL DEVELOPMENT OF ANCIENT MESOPOTAMIANS - Irgashevich, Karimov Basriddin (PT. Antis International Publisher, 2024)
Objective: This study examines the cultural development of ancient Mesopotamia, with a focus on the invention and evolution of writing as a key achievement. Method: A comprehensive review of archaeological evidence, cuneiform inscriptions, and historical texts was conducted to analyze the origins and impact of early writing systems in Mesopotamia. Comparative analysis with contemporaneous cultures was also utilized to assess the uniqueness and influence of Mesopotamian writing. Results: The invention of writing by the Sumerians in the 4th millennium BC marked a transformative development in human history. Initially pictographic, the script evolved into a complex system of symbols (cuneiform), facilitating administrative, legal, and cultural exchanges. Writing was integral to the administration of city-states, religious practices, and the preservation of knowledge, contributing significantly to the intellectual foundations of subsequent civilizations. Novelty: This research underscores the critical role of writing in the cultural and societal advancements of Mesopotamia, highlighting its impact on governance, literature, and the transmission of knowledge. The study also provides new insights into the adaptability and influence of Sumerian writing in shaping the broader ancient world.